Patterns of Coordinated Anatomical Change in Human Cortical Development: A Longitudinal Neuroimaging Study of Maturational Coupling - Raznahan, Armin (Neuron, 2011)
Understanding of human structural brain development has rapidly advanced in recent years, but remains fundamentally “localizational” in nature. Here, we use 376 longitudinally acquired structural brain scans from 108 typically developing adolescents to conduct the first study of coordinated anatomical change within the developing cortex. Correlation in rates of anatomical change was regionally heterogeneous, with fronto-temporal association cortices showing the strongest and most widespread maturational coupling with other cortical areas, and lower-order sensory cortices showing the least. Canonical cortical systems with rich structural and functional interconnectivity showed significantly elevated maturational coupling. Evidence for sexually dimorphic maturational coupling was found within a frontopolar-centered prefrontal system involved in complex decision-making. By providing the first link between cortical connectivity and the coordination of cortical development, we reveal a hitherto unseen property of healthy brain maturation, which may represent a target for neurodevelopmental disease processes, and a substrate for sexually dimorphic behavior in adolescence.